Langmuir and Freundlich Equation Test on Methylene Blue Adsorption by Using Coconut Fiber Biosorbent - Anselmus Boy Baunsele; Hildegardis - Missa (Walisongo Journal of Chemistry, 2021)
Methylene blue is a cationic dye often used for various industries. Methylene blue waste harms aquatic biota. Most ways have been done to reduce the methylene blue pollution that includes photocatalytic, electrochemical, and adsorption. This study aimed to reduce the impact of methylene blue pollution on the aquatic environment and to test the adsorption isothermal for methylene blue adsorption using coconut fiber. The abundant coconut fiber waste around the Kupang city was taken and prepared to be used as an adsorbent. The characterization results showed that the active groups in cellulose were clearly described on the FTIR spectra which showed the presence of  O-H vibrations at 3296.35 cm-1, C-O vibrations were seen at 1267.23 and 1060.85 cm-1, at wavelengths 1608.63 cm-1 and 817.72 cm-1 there is a vibration from the C=C bond, while the C-H vibration appears at a wavelength of 2939.52 cm-1. The results of this research analysis showed that the adsorption of methylene blue according to the Langmuir isotherm indicated by the value of the equation of the straight line R2 being one and the direction of the curve depicting occurring the effective adsorption. The maximum adsorption capacity was 4.467 mg g-1 with the percentage of methylene blue adsorbed at 99.3%. Adsorption occurs chemically with an energy of 27.29 kJmol-1 so it can be determined that the adsorption occurs with a monolayer mechanism.